Patients' Knowledge of Key Messaging in Drug Safety Communications for Zolpidem and Eszopiclone: A National Survey. Issue 3 (2019) - Kesselheim, Aaron S.; Sinha, Michael S.; Rausch, Paula; Lu, Zhigang; Tessema, Frazer A.; Lappin, Brian M.; Zhou, Esther H.; Dal Pan, Gerald J.; Zwanziger, Lee; Ramanadham, Amy; Loughlin, Anita; Enger, Cheryl; et al.
Abstract : Drug Safety Communications (DSCs) are used by the Food and Drug Administration (FDA) to inform health care providers, patients, caregivers, and the general public about safety issues related to FDA-approved drugs. To assess patient knowledge of the messaging contained in DSCs related to the sleep aids zolpidem and eszopiclone, we conducted a large, cross-sectional patient survey of 1, 982 commercially insured patients selected by stratified random sampling from the Optum Research Database who had filled at least two prescriptions for either zolpidem or eszopiclone between July 1, 2012 and June 30, 2013. Among the 594 respondents (32.7% response rate), two-thirds reported hearing generally about drug safety information prior to starting a new drug, with the remaining one-third "rarely" or "never" hearing such information. Providers and pharmacists were primary sources of drug safety information. Two-thirds of zolpidem users and half of eszopiclone users reported having heard about the related DSC messages, ability to accurately identify the major factual messages was limited (overall median 2 correct out of 5, with men and those reporting higher educational level scoring higher [2/5 vs. 1/5, p=0.001]). Respondents reacted to new drug safety information about their sleep aids by reporting that they would want to learn about alternative ways to help them sleep (70%) and seek out more information about the safety of their specific sleeping pill (59-78%). Opportunities may exist for the FDA to work with providers and pharmacies to help ensure the DSC information is more widely received and is more fully understood by those taking the affected medications.